Evaluation of Inventory Accounting Information Systems Using Pieces Method: A Study on SIMEDi’s Application - Sauri, Sofyan; Firmandani, Wahyu; Suteja, Diana; Puspitasari, Leny; Putri, Tesa Eranti; Eriani, Izmi Dwira (IPB University, 2024)
This study aims to evaluate the SIMEDi inventory accounting information system in Perumda Perkebunan Kahyangan Jember. The method used in this study is a case study with a PIECES analysis approach. Data collection techniques were carried out by conducting interviews with the board of directors and staff who have access to SIMEDi. The PIECES approach involves six evaluation variables, namely performance, information, economic, control and security, efficiency and service. The results of the evaluation showed that SIMEDi meets the six PIECES variables, namely: all SIMEDi features have been running well (performance variables), the information produced by SIMEDi has met reliable input process output (information variables), the benefits generated from the implementation of SIMEDi are greater than the costs incurred (economic variables), SIMEDi has provided adequate system control to maintain the reliability of the information produced (control and security variables), SIMEDI makes inventory management at Perumda Kahyangan more efficient (efficiency variables), and SIMEDi is very user friendly and easy to operate (service variables). The SIMEDi Inventory Accounting Information System provides convenience and reliability for Perumda Perkebunan Kahyangan in managing inventory, especially for making appropriate and accurate decisions.